Fishing Season of Large Tuna from Purse Seine Fishery in Tumumpa, Manado, North Sulawesi - Bram Setyadji; Umi Chodriyah (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Knowledge on seasonal fishing pattern is essential in fisheries research in order to increase the effectiveness of fishing and at the same time protecting the fishing ground from excessive fishing practices. Determining the seasonal fishing pattern of large pelagic fishes, namely large tuna (yellowfin and bigeye), small tuna (mackerel) and skipjack tuna were the objective of this study. Data from the 2013-2015 fishing operation time series were used to analyze the fishing season using the percentage average per unit effort (CPUE) method. The main focus of this study was purse seine fishery. The research showed that high fishing season of large pelagic fishes allegedly occurred during May to July, which reached its peak on May. On the other hand, low fishing season occurred during January to April, with the lowest on March. There were similarities between large tuna, small tuna and skipjack in term of their seasonal fishing pattern, although they did not show any good correlation (r<0.5). This might due to fact that even tough large tuna, small tuna and skipjack tuna shared the same ecological niche but apparently, they did not show any interaction (symbiosis) but competition.